Preliminary Screening of the Phytochemical Composition, Antioxidant and Antimicrobial Activity of the Twigs of Prosopis africana Used as Chewing Stick in Benin Republic - OLAYE, Théophile; TCHOBO, PAUL FIDÈLE; CHABI, NICODÈME WOROU; Koudokpon, Hornel; SESSOU, PHILIPPE; ALITONOU, GUY ALAIN; AVLESSI, FÉLICIEN; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2020)
The present work was devoted to the evaluation of the chemical and antimicrobial potential of the stems of Prosopis africana. Standard techniques described in the literature were used to analyse the phytochemicals. The antioxidant activity was carried out by DPPH and FRAP methods and antimicrobial activity, by the diffusion method. Many secondary metabolites like tannins, steroids, coumarins, flavonoids, mucilage and alkaloids were identified in the different extracts of this plant. The semi-ethanolic extract presented the highest total phenolic content which is of 124.142 ± 3.535 mg eqGA/gCE whereas the ethanolic extract had the highest content of flavonoid with values of 124.708 ± 5.595 mg eqC/gCE. The ethanolic extract of this plant exhibited a good ability to inhibit the DPPH radical and a good ability to reduce ferric Fe3+ ions to ferrous Fe2+ ion and this could be explain by it good content in phenolic compounds. The ethanolic extract was the only one that was able to inhibit the strains used in this study. MICs and MBCs ranged from 12.500 to 25.000 mg / mL.The same extract was able to inhibit Candida albicans, a strain that is known to be implicated in oral diseases with a MIC of 12.500 mg/mL.
Keywords: Phytochemical; Antimicrobial; Antioxidant; Chewing stick; Oral hygiene